Davies, Florence (1995). Introducing Reading. - Sonia Maria Gomes Ferreira (Ilha do Desterro)
Arising at a time of unprecedented growth of interest in fostering critical thinking, Introducing Reading offers a clear introduction and thorough account of contemporary developments in the field of reading. While overtly focusing on the special demands of social and human aspects of the reading practice, the issues raised have crucial resonance in the sphere of critical reading. Explicitly addressed to teachers of mother tongue and foreign language contexts, the book claims to elaborate on aspects of reading which have received meager attention to date: individual readers engaged in different real-world reading tasks, the social contexts where such readers engage and interact with texts, and the nature and variety of texts, here regarded as “participants” in the interaction between reader and writer. To this extent, the book successfully reaches the ambitious aim of “socializing and humanizing reading and the teaching of reading” (p. xi).